Diverse Novel Stable Traveling Wave Solutions of the Advanced or Voltage Spectrum of Electrified Transmission Through Fractional Non-linear Model - Yue, Chen; Wu, Li; Mousa, A. A.; Lu, Dianchen; Khater, Mostafa M. A. (Frontiers in Physics, 2021)
This paper analyzes the exact solutions of Oliver Heaviside 1880's compliance fractional nonlinear time-space telegraph (FNLTST)equation via three unapplied analytical schemes. The solutions obtained define the advanced or voltage spectrum of electrified transmission, with day--to--day distances from the electrified communication or the application of electromagnetic waves. Many new solutions are obtained, and three distinct styles of drawings are introduced (two, three--dimensional, and density plots). Furthermore, stability characterization of the solutions is addressed using the properties of the Hamiltonian system. The manuscript's originality is shown by matching the solutions built with solutions produced previously using various analytical methods. Overall, the three systems' success demonstrates their quality, intensity, and capacity to cope with several different types of nonlinear evolutionary equations.